Pendampingan Pembuatan Serbuk Instan Metode Kristalisasi Kombinasi Daun Buas-Buas (Premna serratifolia L.) dan Jahe Merah (Zingiber officinale var. Rubrum): Assistance in Making Instant Powder Using the Crystallization Method of Combination of Buas-Buas Leaves (Premna serratifolia L.) and Red Ginger (Zingiber officinale var. Rubrum) - Isnindar, Isnindar; Anastasia, Desy Siska; Desnita, Rise (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The limited knowledge of the community regarding the manufacture of instant powdered beverage products from natural ingredients, especially among grade XI students at SMAN 11 Pontianak, provides the background for implementing community service activities (PKM). A lack of knowledge, information, and skills makes TOGA processing ineffective and inefficient. One way to process plants into marketable products is to make instant powdered beverage products. Medicinal plants that will be used as ingredients for instant powdered beverages are the leaves of the wild-born and red ginger. These plants have good properties in maintaining body health. The purpose of this community service program is to increase the community's knowledge, information, and skills, especially among grade XI students at SMAN 11 Pontianak, through training and mentoring programs in making instant powdered beverage products, a combination of wild-born leaves and red ginger. The method used is training in making instant powdered beverage products, then mentoring in making instant powdered beverage products, and providing material presentations to students of grade XI of SMAN 11 Pontianak on how to determine the composition and processing of ingredients to produce quality instant powdered beverage products, to increase the knowledge of students of grade XI of SMAN 11 Pontianak. The posttest results showed an increase in participants' knowledge after receiving the material explanation by 55.42%, from 60.61% to 84.2%, which is classified as very good. The mentoring activity on making instant powdered beverage products at SMAN 11 Pontianak demonstrated enthusiasm and excellent understanding among the participants.